Divisi Infeksi dan Penyakit Tropis Infeksi Measles Pada Anak Perempuan 3 Tahun - Rifani, Muhammad; Pelupessy, Ninny Meutia; Artati, Ratna Dewi; Baso, Aidah Juliaty A. (Universitas Pahlawan Tuanku Tambusai, 2024)
Measles is a highly contagious infection that spreading especially in populations that are dense with exhibit low immunity. The best protection is active immunization during childhood. Without vaccination, measles morbidity and mortality is very high. Here, we report a case of a 3-year-old child presenting with fever, malaise, productive cough, runny nose, conjunctivitis with Koplik's spot and maculopapular rash. Suspected measles infection is confirmed by positive measles virus IgM antibody and reverse transcriptase polymerase chain reaction in blood and urine. The patients are isolated and treated symptomatically. Management is given to these patients includes educating the patient's parents about the patient's illness and complications of the disease and the provision of medical form of infusion RL 16 ml / hour, Paracetamol 150 mg / hour, Ambroxol 7 mg / 8 hours, and Vitamin A 200.000 IU for 2 days. Guidelines for measles immunization in infants given one at the age of 9 months given the measles antibody toddlers whose mothers had decreased at the age of 9 months. Methode : This case study was researched only in the form of a single unit, but was analyzed in depth covering a fairly wide range of aspects. Conclution : In young patients, complete recovery was achieved within two weeks. In patients with fever and maculopapular rash and fatigue, measles should be considered even in all children patients. Early diagnosis, followed by isolation and patient registration are important measures to prevent local outbreaks.